Are long fire-free periods needed to maintain the endangered, fire-recruiting shrub Arctostaphylos morroensis (Ericaceae)? - Odion, D.; Tyler, C. (Conservation Ecology, 2002)
Morro manazanita (Arctostaphylos morroensis) is a distinctive shrub restricted to a small area along the coast of California, USA. This endangered species faces two opposing fire-related extinction risks: (1) adults are killed by fire, and (2) recruitment opportunities only occur with fire. These strongly limit the capacity of this, as well as other obligate-seeding species, to recover from a population decline, which may result if there is an inadequate amount of time between fires for replenishment of sufficient seed populations. Using a prescribed burn, we tested whether the size of the seed bank that had accumulated in a 40-yr-old stand would prove adequate for maintaining A. morroensis population sizes through fire. Prior to the burn, we found ~11,000 seeds/m2 in the soil, mostly in the top 5 cm. However, the number of viable seeds was substantially lower (334 seeds/m2), and less than one-third of these survived the experimental fire (99 seeds/m2). Germination occurred only in the first two wet seasons after the fire, and may have been adequate to replace the number of A. morroensis present before the burn. However, most seedlings did not survive their initial summer drought. After three years, the new population of A. morroensis was less than half the size of the parent population. Further mortality is expected because the remaining seedlings are highly clumped. We conclude that A. morroensis may require considerably longer than 40 years to establish an adequate seed bank to compensate for mortality and prevent population decrease or local extinction. This prolonged risk is perhaps explained by specialization of this species to a historic regime of relatively infrequent fire. There are many obligate-seeding species in fire-prone shrublands that may not be resilient to a regime of fire more frequent than that with which they evolved.
Keywords: Arctostaphylos morroensis; California coast; endangered species; fire-dependent germination; fire-related extinction risk; maritime chaparral; Morro manzanita; obligate-seeder; postfire seedling recruitment; seed bank; shrublands; viable seed